Prognostyczna analiza progu rentowności - Nowak, Edward (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article treats the breakeven point analysis in the dynamic approach. In this approach the breakeven point is being marked for the successive periods of the researched time interval. It creates the possibility of the fixing of the general developmental tendencies. Through the extrapolation of the trend function the prognosis of the value and quantity of the breakeven point are marked. The proposed procedure is illustrated by the empirical example. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 257-263